2011
DOI: 10.1111/j.1365-2559.2011.03800.x
|View full text |Cite
|
Sign up to set email alerts
|

High-level cytoplasmic cyclin D1 expression in lymph node metastases from prostate cancer independently predicts early biochemical failure and death in surgically treated patients

Abstract: The subcellular location of cyclin D1 expression in prostate cancer is linked to specific clinical courses. Survival stratification according to biomarker expression in metastases indicates an important role for tumour sampling from these tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 50 publications
(95 reference statements)
3
13
0
1
Order By: Relevance
“…Previous studies (6,7) have shown no relationship between cyclin D1 expression and the Gleason score, but, in this study, we found a positive statistically significant association between the Gleason score and cyclin D1 expression, with high-grade tumors displaying high cyclin D1 expression compared with low-grade tumors, in agreement with a study conducted by Emin Özbek et al (21). However, unlike our study, other studies may not have determined the optimal cut-off value using ROC curve analysis, such as the Emin Özbek study, that showed positive correlation between Gleason score and cyclin D1.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Previous studies (6,7) have shown no relationship between cyclin D1 expression and the Gleason score, but, in this study, we found a positive statistically significant association between the Gleason score and cyclin D1 expression, with high-grade tumors displaying high cyclin D1 expression compared with low-grade tumors, in agreement with a study conducted by Emin Özbek et al (21). However, unlike our study, other studies may not have determined the optimal cut-off value using ROC curve analysis, such as the Emin Özbek study, that showed positive correlation between Gleason score and cyclin D1.…”
Section: Discussionsupporting
confidence: 93%
“…The mean age and mean preoperative PSA levels were similar to those reported in previous studies (7,9,10). The predominant pathological TNM stage was pT2c (60%), but this was different from previous studies by Freedland et al (11) (pT2a, 34%) and Makarov et al (12) (pT1c, 77%).…”
Section: Discussionsupporting
confidence: 88%
“…Molecular parameters that have been described to be linked to metastasis and cancer-related death in patient cohorts describing at least 100 patients with unfavorable events include p53 (41,42), bcl-2 (41), microvessel density (41), Ki-67 (42), CD10 (43), cyclin D1 (44), telomere length (45), HER2-neu (46), Stat5a/b (47), AMACR (48), HSP-27 (49), and MDM2 (42). All these parameters have also been linked to PSA recurrence in the respective studies (44,(46)(47)(48).…”
Section: Discussionmentioning
confidence: 99%
“…Cyclin D1 is one of the key regulators in the control of cell cycle progression from G0-G1 to S phase, and inducible Cyclin D1 forms a complex with CDK4/6, which phosphorylates the retinoblastoma tumor suppressor protein (33), sequestrates pRb growth inhibitory effects on E2F and enables E2F transcription factors to transcriptional regulate genes required for entry into the DNA synthetic phase (S) of the cell division cycle (34). Cyclin D1 overexpression prevails over that of Cyclin D2 and D3 (35), and overexpression of Cyclin D1 is one of the cancer features and is responsible for inducing excessive cellular proliferation in many human cancers, including bladder cancer (4), breast (36), cervix (37), colon (38), prostate (39), and skin cancer (40). Thus, Cyclin D1 is one of the most frequently altered cell cycle regulating protein in cancers and therefore, is a potential therapeutic target (41, 42).…”
Section: Discussionmentioning
confidence: 99%